2009
DOI: 10.1118/1.3152867
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative contrast‐enhanced myocardial perfusion magnetic resonance imaging: Simulation of bolus dispersion in constricted vessels

Abstract: Quantification of myocardial blood flow (MBF) by means of T1-weighted first-pass magnetic resonance imaging (MRI) requires knowledge of the arterial input function (AIF), which is usually estimated from the left ventricle (LV). Dispersion of the contrast agent bolus may occur between the LV and the tissue of interest, which leads to systematic underestimation of the MBF. The aim of this study was to simulate the dispersion along a simplified coronary artery with different stenoses. To analyze the dispersion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 45 publications
5
29
2
Order By: Relevance
“…The mass fraction of the injected contrast agent bolus Y CA can be described by a gamma-variate function at the inlet of our geometry [15, 16, 30] YCA(t,z=0)={a0.75em0.75em(ttnormal00.75em0.75em)bec0.75em0.75em(ttnormal00.75em0.75em)t>tnormal0,normal0ttnormal0, where the parameters have been estimated by fitting the AIF measured inside the LV of a volunteer MRI measurement as a = 1.013 × 10 −3 , b = 2.142, and c = 0.454 s −1 . The parameter t 0 describes the delayed arrival of the bolus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass fraction of the injected contrast agent bolus Y CA can be described by a gamma-variate function at the inlet of our geometry [15, 16, 30] YCA(t,z=0)={a0.75em0.75em(ttnormal00.75em0.75em)bec0.75em0.75em(ttnormal00.75em0.75em)t>tnormal0,normal0ttnormal0, where the parameters have been estimated by fitting the AIF measured inside the LV of a volunteer MRI measurement as a = 1.013 × 10 −3 , b = 2.142, and c = 0.454 s −1 . The parameter t 0 describes the delayed arrival of the bolus.…”
Section: Methodsmentioning
confidence: 99%
“…Calamante et al performed CFD simulations to estimate the dispersion of a contrast agent bolus in cerebral vessels [14]. Previous CFD simulations examining the bolus dispersion in coronary vessels performed by Graafen et al used an idealized single vessel geometry considering both constant [15] and pulsatile [16] flows. Both demonstrated an underestimation of the MBF and an overestimation of the MPR if bolus dispersion is neglected.…”
Section: Introductionmentioning
confidence: 99%
“…This has a direct impact on the accuracy of blood flow estimates. Instead the enhancement from the contrast bolus is typically measured in the LV blood pool or the proximal aorta, but transit through the epicardial vessels is bound to cause some dispersion of the contrast bolus, which may be exacerbated by an epicardial stenosis[49]. One is forced to either neglect this dispersion of the contrast bolus during transit through the epicardial vessels, or assume a fixed relative dispersion.…”
Section: Current Limitationsmentioning
confidence: 99%
“…Assuming nonturbulent flows, simulations have shown that the variance of the mean transit times decreases as the flow rate is increased, indicating that bolus dispersion may be most noticeable during resting conditions rather than hyperemia. 29 Therefore, it is likely that any underestimation of blood flow, resulting from any (unaccounted) bolus dispersion, is less pronounced during hyperemia than at rest. Nonetheless, to definitively address all these limitations requires an animal model of CABG, with validation of CMR-derived perfusion against microsphere determination of MBF in graftsubtended segments.…”
Section: Limitationsmentioning
confidence: 99%
“…However, a recent study examining bolus dispersion in constricted vessels indicates that dispersion is actually more pronounced at rest than at stress. 29 The degree of dispersion of a contrast bolus during transit through a nonstenotic vascular segment, such as a CABG graft, increases in proportion to the variance of the mean transit times. Assuming nonturbulent flows, simulations have shown that the variance of the mean transit times decreases as the flow rate is increased, indicating that bolus dispersion may be most noticeable during resting conditions rather than hyperemia.…”
Section: Limitationsmentioning
confidence: 99%